ANALISIS HUKUM PUTUSAN HAKIM TERHADAP ANGGOTA KPU PANGKAJENE DAN KEPULAUAN - Laia, Famati (LPPM Universitas Nias Raya, 2025)
Violation of the code of ethics for election organizers is a violation of the ethics of election organizers which are based on oaths and/or promises before carrying out their duties as election organizers. The aim is to maintain the independence, integrity and credibility of election organizers who are independent, honest, fair, have legal certainty, orderliness, public order, openness, proportionality, accountability, efficiency and effectiveness. This has been included in Law Number 2 of 2017 concerning the Code of Ethics and Code of Conduct for General Election Organizers of the Republic of Indonesia. Thus, violations of the code of ethics committed by election organizers are inappropriate actions. In this research, the type of research used is normative legal research with a statutory regulation approach, case approach, and using secondary data obtained through secondary legal materials. Then, the data analysis used was a deductive method. Based on the results of research and discussion regarding the legal analysis of the judge's decision on members of the Pangkajene and Islands KPU (study decision number 41-PKE-DKPP/II/2023) it can be concluded that the imposition of permanent dismissal sanctions on members of the Pangkajene and Islands KPU as mentioned in Article 6 paragraph (1) and paragraph (3) letters a, c and f, Article 11, Article 12 letters a, b and c, Article 15 and Article 16 letter e, general election organizer honorary council regulation number 2 of 2017 concerning code ethics and code of conduct for general election organizers. However, the application of this law is not in accordance with Law number 2 of 2019 concerning amendments to the regulations of the honorary council for general election organizers number 3 of 2017 concerning Procedural Guidelines for the Code of Ethics for General Election Organizers. Thus, the researcher considers that imposing a permanent dismissal sanction in the case (study decision number 41-PKE-DKPP/II/2023) is inappropriate. This can make people distrust DKPP as an independent institution. For this reason, researchers hope that DKPP in deciding on violations of the code of ethics will be more thorough and in accordance with applicable laws and regulations.